E-COMMERCE BUSINESS PLAN FOR POULTRY FARMING: TERNAK SEGAR - Shandy Puspita (Jurnal Bina Manajemen, 2019)
Indonesia has very big potency to increase their poultry output. One of the favorite consumed poultry product was chicken and eggs. Government also drive the output of poultry product should be increased every year. But the problem is Indonesia still face the shortage of supply of the poultry products. Despite the import, the market still faces the shortage. Base on this condition, our research focus is on the Ternak Segar business model. There is big opportunity and big market potency that still could be explored in Poultry Product. The challenge itself is how to develop competitive and innovative business products.